Predictive validity of the Boey scoring system for postoperative outcomes in perforated peptic ulcer disease: a prospective study from a tertiary center of Nepal - Shrestha, Samrat; Shrestha, Mecklina; Rai, Prahasan; Maharjan, Suresh (International Surgery Journal, 2025)
Background: Perforated peptic ulcer (PPU) is a surgical emergency with high morbidity and mortality, making risk stratification critical. The Boey score (comorbidity, preoperative shock (SBP <90 mmHg), presentation delay >24 h) is a simple preoperative tool for predicting PPU outcomes. Methods: Authors conducted a prospective observational study (February 2023–Mar 2025) in Kathmandu, including 94 adults (18-80 years) undergoing emergency laparotomy for PPU. We recorded each patient’s demographics and calculated the Boey score. All patients received standard surgical repair (Graham’s patch and lavage). Outcomes were 30-day postoperative morbidity, mortality and hospital stay. Results: Patients (mean age 40.05±18.17 years, 92.6% male) were stratified: Boey 0 (31.9%), Boey 1 (45.7%), Boey 2 (11.7%), Boey 3 (10.6%). Overall morbidity was 42.6%, increasing significantly: 13.3% (score 0), 46.5% (score 1), 72.7% (score 2), 80.0% (score 3) (p<0.001). Overall, 30-day mortality was 9.57%, rising sharply with Boey score: 0% (score 0), 4.65% (score 1), 9.1% (score 2), 60% (score 3) (p<0.001). Boey score ≥2 predicted morbidity with 40.0% sensitivity and 90.7% specificity (AUC=0.755, 95% CI 0.65-0.85). Boey score=3 predicted mortality with 66.7% sensitivity and 95.3% specificity (AUC=0.882, 95% CI 0.76-0.97). The mean hospital stay was 9.0±3.62 days. Conclusions: In this study, a higher Boey score strongly predicted worse postoperative outcomes in PPU. Patients with Boey ≥2 had substantially higher complication and death rates. The simple Boey score is a valid preoperative triage tool for PPU in resource-limited settings.